2017
DOI: 10.3847/1538-4357/aa863a
|View full text |Cite
|
Sign up to set email alerts
|

A Spatially Resolved Study of Cold Dust, Molecular Gas, H ii Regions, and Stars in the z = 2.12 Submillimeter Galaxy ALESS67.1

Abstract: van der (2017) 'A spatially resolved study of cold dust, molecular gas, H II regions, and stars in the z = 2.12 submillimeter galaxy ALESS67.1.', The astrophysical journal., 846 (2). p. 108.Further information on publisher's website:https://doi.org/10.3847/1538-4357/aa863aPublisher's copyright statement: c 2017. The American Astronomical Society. All rights reserved. Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
121
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 91 publications
(143 citation statements)
references
References 132 publications
22
121
0
Order By: Relevance
“…This provides morphological and geometrical evidence for the origin of the DSFG offsets from the M99 relation (see also Chen et al 2017) being consistent with the extreme extinction expected from the compact and intense dust emission for this sample (see Section 4.3), implying that UV emission should be expected not to escape the starbursts.…”
Section: Irx-β Planesupporting
confidence: 56%
“…This provides morphological and geometrical evidence for the origin of the DSFG offsets from the M99 relation (see also Chen et al 2017) being consistent with the extreme extinction expected from the compact and intense dust emission for this sample (see Section 4.3), implying that UV emission should be expected not to escape the starbursts.…”
Section: Irx-β Planesupporting
confidence: 56%
“…While high-resolution studies of the dust continuum emission in SMGs with ALMA have shown that this material appears to be mostly distributed in compact regions (Ikarashi et al 2015;Simpson et al 2015;Hodge et al 2016;Tadaki et al 2017a), the extended sizes revealed by the few resolved CO detections of luminous sources (Riechers et al 2010;Hodge et al 2012;Emonts et al 2016;Chen et al 2017;Dannerbauer et al 2017;Ginolfi et al 2017;Tadaki et al 2017b) challenge the general assumptions of co-spatial interwoven dust and gas generally assumed by other models. Spatially resolved observations of CO and dust continuum emission for homogeneously selected samples and modeling of their interplay, e.g., through radiative transfer approximations, may help to characterize the distributions and physics of dust and gas in the high-redshift ISM.…”
Section: Introductionmentioning
confidence: 93%
“…Due to the high spatial resolution of the data, it is not trivial to estimate the masks on which to apply the CLEAN task. We adopted an iterative cleaning technique (e.g., Chen et al 2017), in order to optimize the mask size estimation to include possible extended low surface brightness emission. Iterative cleaning consists of drawing concentric circular mask regions at increasing radii and applying the CLEAN task and line flux extraction within them.…”
Section: Target Selection Alma Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Another caveat to using FIR continuum emission instead of CO comes from the finding that the dust emission measured by ALMA may not always trace the bulk of the gas distribution. This is made clear by the small sizes of the dust-emitting regions compared to the star-forming regions and the gas as traced by CO emission (e.g., Ivison et al 2011;Riechers et al 2011bRiechers et al , 2014Simpson et al 2015;Hodge et al 2016;Chen et al 2017;Miettinen et al 2017).…”
Section: Introductionmentioning
confidence: 99%